A PROJECT MANAGEMENT GEOINFORMATICS UTILITY FOR HEALTH PROTECTION AND SANITARY DRAWINGS IN GREEN CONSTRUCTIONS - INFRASTRUCTURE WORKS - TILEMACHOS KOLIOPOULOS; SOKRATIS THEOCHARATOS; PANAGIOTIS KOULOUMPIS; CRINA RADU; ION CRISTEA (Journal of Engineering Studies and Research)
This research study analyses the life cycle assessment of different waste management techniques and sanitary drawings in landfilled waste treatment units' biotechnology at Community Health Centres design for the protection of Public Health from biogas emissions, leachate hazardous toxic acids and landfill biomass biodegradation stages. The environmental impact assessment is examined of associative pollution spaces of Community Health Centres minimising the relative public health's risks. Moreover, it examines the significance of phytobioremediation techniques for landfills' heavy metal concentrations and associated risks minimisation. Reclamation works are examined in associated risks minimisation of toxic hazardous concentrations that could enter in water resources, food chain and agricultural resources. A useful geoinformatics utility is presented in this research study for project management of associated infrastructures in green sustainable construction designs; the optimum operation of Health Centres and associated infratructures for the protection of Public Health.